10.24843 Construction of The Verb Sequence Menjuruh in The Classic Malay Language - Madia, I Made; Artawa, Ketut; Pastika, I Wayan; Darma Laksana, I Ketut (e-Journal of Linguistics; Vol 12 No 2 (2018): eJL-July, 2018)
The construction of verbs sequence ‘konstruksi verba beruntun’, which is hereinafter abbreviated to KVB, in this article is defined as a construction without the existence of any linking word and pausing mark (comma). Based on the theory of typology, as far as the complex predicate is concerned, the only KVB menjuruh +V itr (intransitive verb) whose grammatical object functioning as the nucleus argument located after V 2 (the second verb) and KVB menjuruh +V tr (transitive verb) which is not marked by the morphological prefix meng- are identified as having the complex predicate construction ‘kontruksi predikat kompleks’ which is hereinafter abbreviated to KPK. Based on the theory of transformational grammar, the KVB menjuruh , except that identified as KPK, is identified as having the complex clausal construction ‘konstruksi klausa kompleks’, which is hereinafter abbreviated to KKK.